YOUTUBERS SURDOS COMO MARCADORES CULTURAIS: UMA ANÁLISE MULTIMODAL DE PRODUÇÕES CONTEMPORÂNEAS - Ruiz, Luciana Rodrigues (2019)
This thesis, whose theme is “deaf cultural productions”, has the general objective of analyzing cultural markers in the productions of deaf YouTubers in order to enlarge the understanding about the constitution of ways of being deaf in the Contemporaneity. It was sought, with this work, to identify which cultural markers were present in videos of deaf YouTubers published in the last five years; to understand how the cultural markers present in deaf YouTubers videos produce specific ways for the deaf to relate to themselves, to other deaf people and to listeners; to analyze the multimodal resources present in the deaf YouTubers videos from the representational function of the Reading Images in order to verify how these resources are mobilized by the deaf YouTubers in the production of ways of being deaf in the present. To develop the research, we used the Critical Discourse Analysis, more specifically, the discourse as a social practice of Norman Fairclough, the difference under the bias of Cultural Studies, deaf cultural markers and the Reading Images for visual language analysis. The research was descriptive/interpretive, using seven videos from four deaf YouTubers, whose themes were the relationships between deaf and hearing, the right to be deaf, the day of the deaf, teaching the Brazilian Sign Language, deaf leaders and music for the deaf. With this, the following results were achieved: the only marker that does not appear in the selected videos is the time; the other markers appear in most videos, which shows that they are inherent to the enunciations of the deaf person active in the deaf community. To analyze the videos, deaf cultural markers and the representational function were used. It is concluded from the research that deaf YouTubers are becoming a cultural marker since they are opinion makers, and they encourage and stimulate the perception of deafness as a difference and thus influence the ways of being.